1993
DOI: 10.1172/jci116538
|View full text |Cite
|
Sign up to set email alerts
|

Effect of fasting, hypocaloric feeding, and refeeding on the energetics of stimulated rat muscle as assessed by nuclear magnetic resonance spectroscopy.

Abstract: A previous study suggested that muscles from hypocalorically fed rats were limited in their ability to rephosphorylate ADP. During muscle contraction hydrolysis of ATP results in an increase in phosphorus, free ADP, AGATp, and a reduction in phosphocreatine levels that is reversed during rest by rephosphorylation of ADP to ATP and the resynthesis of phosphocreatine by ATP. We therefore hypothesized that these changes would be restored more slowly during postcontraction rest in hypocalorically fed rats as compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
0
1

Year Published

1998
1998
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(13 citation statements)
references
References 22 publications
1
11
0
1
Order By: Relevance
“…mitochondrial proteins. Previous studies suggest that muscle cell energetics are altered by protein–energy restriction, showing altered mitochondrial function and slower rephosphorylation of ADP in the skeletal muscle of malnourished rats . Here, and in line with this observation, undernutrition reduced mitochondrial biogenesis and impaired the activity of the Krebs cycle and the activity and gene expression of the mitochondrial electron transport chain in muscle (complex II).…”
Section: Discussionsupporting
confidence: 84%
“…mitochondrial proteins. Previous studies suggest that muscle cell energetics are altered by protein–energy restriction, showing altered mitochondrial function and slower rephosphorylation of ADP in the skeletal muscle of malnourished rats . Here, and in line with this observation, undernutrition reduced mitochondrial biogenesis and impaired the activity of the Krebs cycle and the activity and gene expression of the mitochondrial electron transport chain in muscle (complex II).…”
Section: Discussionsupporting
confidence: 84%
“…It is known that corticosteroids therapy and also malnutrition may induce selective type IIb ®bre atrophy (Russell et al, 1983;van Balkom et al, 1994). Furthermore, malnutrition is associated with altered energy generation in the mitochondria (ie impaired rephosphorylation of ADP in the muscle) (Mijan de al Torre et al, 1993) and with relative loss of muscle creatine and phosphorus in relation to ATP (Thompson et al, 1998). Jeejeebhoy suggested that ATP generation in muscle may be abnormal despite normal body composition in these patients (Jeejeebhoy, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Animais jovens sub-metidos à desnutrição e à posterior recuperação nutricional mantêm o agravo prévio de ultra-estrutrura de mitocôndrias 44 e mantêm a limitação da refosforilação do ADP 45 . Esses fatos indicam persistência da disfunção mitocondrial, apesar da recuperação nutricional.…”
Section: Discussionunclassified